Effects of tourism upon the economy of small and medium-sized European cities: Cultural tourists and 'the others' - Barbara Del Corpo; Ugo Gasparino; Elena Bellini; William Malizia (Fondazione Eni Enrico Mattei (FEEM), 2008)
The paper presents the results of the application of an Input-Output-based approach for the estimation of direct, indirect and induced effects of tourist spending on local economies, in a static partial equilibrium setting. The methodology has been successfully applied in three case studies Bergen (Norway), Elche (Spain), Syracuse (Italy) , in the framework of the 6th FP project PICTURE (Pro-active management of the Impact of Cultural Tourism upon Urban Resources and Economies), in order to quantify the monetary impact of cultural tourism upon urban economies. The analysis was carried out in two major steps: firstly, interviews to tourists in each case study city, in order to estimate the scale and variability of the spending patterns of different profiles of visitors (e.g., culture-driven vs. leisure tourists); secondly, application of the Input-Output model of the economy of concern (eventually re-scaling the matrix at the Region or County level) to quantify the effects of tourist expenditure on sales, income and employment for the several impacted economic sectors. Tourists driven by cultural interest are often assumed, in literature, to have a higher than average income and to spend more on holiday. The paper reports the main findings of the analysis, discussing them against the 'cultural tourist' stereotype. The analysis aims at assisting local decision makers in identifying the value of different tourist typologies to their region, in understanding how different sectors of local economy and society can benefit from tourism and in determining how to maximise, or more equally redistribute, the positive impact.
Keywords: C67; R15; L83; D12; 330; Tourism; Cultural Tourism; Economic Impacts; Input-Output Analysis; Tourismus; Städtetourismus; Makroökonomischer Einfluss; Input-Output; Bergen; Elche (Spanien); Sizilien